LINGUISTIC AND CULTURAL FEATURES OF LITERARY TRANSLATION (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
When translating a literary text, it is necessary to convey the stylistic features of the original text as fully as possible and preserve its national and cultural flavor. Due to the fact that the pragmatic potential is realized in different languages in different ways, the translator has to resort to different strategies in order to achieve an equivalent communicative effect in the target language. Currently, literary texts are being translated to a large extent, and the need to preserve linguistic and cultural features determines the relevance of the topic articles.